2022
DOI: 10.48550/arxiv.2202.02471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Few-shot Learning as Cluster-induced Voronoi Diagrams: A Geometric Approach

Abstract: Few-shot learning (FSL) is the process of rapid generalization from abundant base samples to inadequate novel samples. Despite extensive research in recent years, FSL is still not yet able to generate satisfactory solutions for a wide range of real-world applications. To confront this challenge, we study the FSL problem from a geometric point of view in this paper. One observation is that the widely embraced ProtoNet model is essentially a Voronoi Diagram (VD) in the feature space. We retrofit it by making use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Furthermore, data enhancement for fine-tuning the feature backbone is essential when domain divergence occurs between the training and testing sets. Chunwen Ma et al [25] studied the few-shot classification problem from a geometric perspective and they found that the essence of a prototype network can be regarded as a Voronoi Diagram in the feature space. Based on this perspective, they proposed Cluster-induced Voronoi Diagram to improve the accuracy and robustness of the few-shot image classification.…”
Section: Related Work a Few-shot Learningmentioning
confidence: 99%
“…Furthermore, data enhancement for fine-tuning the feature backbone is essential when domain divergence occurs between the training and testing sets. Chunwen Ma et al [25] studied the few-shot classification problem from a geometric perspective and they found that the essence of a prototype network can be regarded as a Voronoi Diagram in the feature space. Based on this perspective, they proposed Cluster-induced Voronoi Diagram to improve the accuracy and robustness of the few-shot image classification.…”
Section: Related Work a Few-shot Learningmentioning
confidence: 99%